When social norms and self-image conflict: A public good experiment with social comparison feedback - Serhiy Kandul; Bruno Lanz (University of Neuchâtel, Institute of Economic Research (IRENE), 2018)
Social comparison feedback, i.e. informing people about the behavior of others, has been shown to influence prosocial behavior in many domains, including tax compliance and energy conservation. We argue that heterogeneity in people's (un)willingness to consult the corresponding information mitigates the effect of these interventions, and hypothesize that self-image concerns can induce people to deliberately ignore feedback about own behavior. We substantiate this idea by introducing social comparison feedback in a standard public good game, and study conditions in which subjects can elect to consult or deliberately avoid feedback information. Our results show that information avoidance is three times higher for feedback on own contributions as compared to feedback on group-level contributions. We further show that social feedback information affects contributions through within-group conditional cooperation, with subjects who choose to ignore individual feedback contributing to a faster breakdown of within-group cooperation.
Keywords: C91; D12; D62; D91; H41; Q41; 330; Social comparison feedback; Deliberate ignorance; Public good game; Social norms; Self-image concerns; Prosocial behavior; Externalities